6-Methylpyridin-2-amine - Draguta, Sergiu (International Union of Crystallography, 2012)
In the title molecule, C(6)H(8)N(2), the endocyclic angles are in the range 118.43 (9)–122.65 (10)°. The molecular skeleton is planar (r.m.s. deviation = 0.007 Å). One of the two amino H atoms is involved in an N—H⋯N hydrogen bond, forming an inversion dimer, while the other amino H atom participates in N—H⋯π interactions between the dimers, forming layers parallel to (100).